Small guanine nucleotide-binding protein Rho and myocardial function - REN Jun; FANG Cindy X (Acta Pharmacologica Sinica; Vol 26, No 3 (March 2005): Acta Pharmacologica Sinica, 2016)
RhoA and Rho-kinase (ROCK) participate in a wide variety of cell signal functions such as cell growth, smooth and cardiac muscle contraction, cytoskeleton rearrangement, cell migration and proliferation. In vascular smooth muscle cells, RhoA and ROCK play an important role in Ca2+ sensitization and regulate vascular smooth muscle tone. In the heart, RhoA and ROCK mediate hypertrophic response leading to cardiac hypertrophy. Recent cellular and molecular biology studies using ROCK inhibitors such as Y-27632 and fasudil have indicated a pivotal role of the RhoA-ROCK cascade in many aspects of cardiovascular function such as cardiac hypertrophy and ventricular remodeling following myocardial infarction. Inhibition of the RhoA-ROCK signaling pathway may be a suitable target for a number of cardiovascular diseases including hypertension, atherosclerosis, diabetes and hypertrophic heart failure. This review focuses on the current understanding of the RhoA-ROCK signal pathway in heart diseases and discusses the use of ROCK inhibitors as therapeutic agents for heart diseases ranging from hypertensive cardiomyopathy to heart failure.